Investigating the car-body vibration of high-speed trains under different operating conditions with full-scale tests. Issue 2 (1st February 2022) - Liu, Dongrun; Li, Tian; Meng, Shi; Lu, Zhaijun; Zhong, Mu
Abstract : An in-depth understanding of car-body vibration characteristics is the key to developing more reasonable operational safety and discomfort evaluation indicators. However, few scholars or research institutions have focused on this topic, and the car-body vibration characteristics that are caused by different complex aerodynamic factors are not clear. Therefore, in this study, different train car-body vibrations under different conditions were investigated using full-scale tests from 2014 to 2016. The results revealed that the car-body vibration for different aerodynamic conditions was mainly low-frequency rolling and traversing motion below 1 Hz, and the primary frequency was close to the car-body lower-centre rolling natural frequency. In addition, the evaluations of the train operational safety and the vibrational comfort could be considered coupled under strong wind conditions. There was a strong line relationship between the car-body roll angle and the train overturning coefficient under strong wind conditions, hence, predicting the train's overturning risk by the car-body roll angle was feasible.